2021
DOI: 10.1007/978-3-030-82095-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Delays at Level Crossings in the United States: Addressing the Need for Multi-Objective Resource Allocation

Abstract: The level crossings in the United States experience a significant number of accidents every year. The accidents can be reduced with the application of various countermeasures (e.g., traffic signal preemption, flashing lights, barrier cubs, gates). However, the application of countermeasures for all the level crossings in the United States is not feasible due to monetary limitations. Moreover, each countermeasure has a unique level of effectiveness and installation cost (e.g., the most effective countermeasures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In the Highway-Railway Grade Crossing Action Plan and Project Prioritization (Rutter et al, 2016), states are required to identify "specific solutions for improving safety at crossings, including highway-railway grade crossing closures or grade separations" (Page 1). By using a cost and benefit analysis, the action plan provides an evaluation of nine crossing improvements.…”
Section: Federal Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Highway-Railway Grade Crossing Action Plan and Project Prioritization (Rutter et al, 2016), states are required to identify "specific solutions for improving safety at crossings, including highway-railway grade crossing closures or grade separations" (Page 1). By using a cost and benefit analysis, the action plan provides an evaluation of nine crossing improvements.…”
Section: Federal Guidelinesmentioning
confidence: 99%
“…Kavoosi et al (2020) developed two optimization models for resource allocation among highway-rail grade crossings to minimize the overall hazard and the overall hazard severity, taking into account the available budget limitations. Singh et al (2022) and Pasha et al (2022) presented a framework for multi-objective resource allocation to minimize the number of crashes and the total delay at level crossings. Using case studies in Florida, they demonstrated superiority of the exact optimization method and provided insights for railway authorities and other stakeholders involved in crossing safety improvements.…”
Section: Other Studiesmentioning
confidence: 99%